2006
DOI: 10.1590/s1516-89132006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of short wave therapy equipment based on brazilian standards

Abstract: Short Wave Diathermy (SWD) equipment is used in physiotherapy and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
3
2
0
1
Order By: Relevance
“…The results of the present study are in agreement with those reported by Gruber et al4 ) , who showed that 75% of the pieces of equipment they evaluated were neither grounded nor working well. On the other hand, Shields et al17 ) reported that all the pieces of equipment they evaluated were within the limits of normality in terms of electrical standards.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the present study are in agreement with those reported by Gruber et al4 ) , who showed that 75% of the pieces of equipment they evaluated were neither grounded nor working well. On the other hand, Shields et al17 ) reported that all the pieces of equipment they evaluated were within the limits of normality in terms of electrical standards.…”
Section: Discussionsupporting
confidence: 92%
“…However, only capacitive plates or Schliephake electrodes are commercially available in Brazil. In the present study, plate-type electrode was the most widely used by the interviewees, a finding also reported by Gruber et al 4 ) , who reported that 65% of their subjects used this type of electrode, and by Shields et al 8 ) , who reported that 80% and 65% of their subjects used, respectively, inductive and capacitive electrodes. These findings are different from those of the study by Shah et al 9 ) , who found that 65% of their subjects used inductive electrodes and only 10% used capacitive ones, thus showing that the variability in the use of different types of electrodes is related to their availability in the market, as well as to their costs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Em um estudo feito por Gruber & Gewehr foram ensaiados onze modelos de equipamentos de sete fabricantes diferentes e todos operavam em 27120 kHz. [55]…”
Section: Equipamento De Terapia Por Ondas Curtasunclassified